Integrating clinical, imaging, and cytopathological data in lymph node fine needle aspiration biopsy : from the Sydney system to the World Health Organization reporting system for lymph node, spleen, and thymus cytopathology - Cozzolino, Immacolata; Barroca, Helena; Bode-Lesniewska, Beata; Calaminici, Mariarita; Ehinger, Mats; Field, Andrew S. (Journal of the American Society of Cytopathology, 2026)
Introduction: Accurate evaluation of lymphadenopathy requires a multidisciplinary approach integrating clinical, laboratory, and imaging data, particularly ultrasound, before and during fine-needle aspiration biopsy (FNAB). Historically, the lack of standardized reporting systems has limited the reproducibility and clinical acceptance of lymph node FNAB. This review focuses on lymph node cytopathology, which currently is supported by a stronger evidence base and more consistent integration into diagnostic algorithms, than splenic or thymic lesions. Materials and methods: The Sydney system (2020) and the subsequent World Health Organization (WHO) reporting system for lymph nodes, spleen, and thymus cytopathology (2024) (WHO system) provide a structured, evidence-based framework for cytopathological evaluation. The WHO system retains the 5 diagnostic categories of the Sydney system—inadequate, benign, atypical, suspicious for malignancy, and malignant—while defining cytomorphological diagnostic criteria, standardizing terminology, and defining category-specific risks of malignancy. It emphasizes clinicopathological correlation and the use of ancillary techniques, including immunocytochemistry, flow cytometry, and molecular studies, and includes specific considerations for pediatric lymphadenopathy. Results: Implementation of the WHO system improves diagnostic accuracy, interobserver reproducibility, and communication between cytopathologists and clinicians. The interventional cytopathologist plays a central role through image-guided FNAB and rapid on-site evaluation, ensuring sample adequacy and appropriate triage for ancillary testing. Conclusions: By integrating cytomorphological, clinical, imaging, and ancillary data within a standardized, risk-based framework, the WHO system reinforces the pivotal role of FNAB in the diagnostic management of lymphadenopathy and establishes a globally harmonized standard for lymph node cytopathology.
Keywords: Ancillary studies; Fine-needle aspiration biopsy; Interventional cytopathologist; Lymph node; Risk of malignancy; WHO reporting system for cytopathology